Group 3 innate lymphocytes make a distinct contribution to type 17 immunity in bladder defence - Alexandra M. Riding; Kevin W. Loudon; Andrew Guo; John R. Ferdinand; Laurence S.C. Lok; Nathan Richoz; Andrew Stewart; Tomas Castro-Dopico; Zewen Kelvin Tuong; Remi Fiancette; Georgina S. Bowyer; Aaron Fleming; et al. (iScience, 2022)
Summary: Bladder infection affects a hundred million people annually, but our understanding of bladder immunity is incomplete. We found type 17 immune response genes among the most up-regulated networks in mouse bladder following uropathogenic Escherichia coli (UPEC) challenge. Intravital imaging revealed submucosal Rorc+ cells responsive to UPEC challenge, and we found increased Il17 and IL22 transcripts in wild-type and Rag2−/− mice, implicating group 3 innate lymphoid cells (ILC3s) as a source of these cytokines. NCR-positive and negative ILC3 subsets were identified in murine and human bladders, with local proliferation increasing IL17-producing ILC3s post infection. ILC3s made a more limited contribution to bladder IL22, with prominent early induction of IL22 evident in Th17 cells. Single-cell RNA sequencing revealed bladder NCR-negative ILC3s as the source of IL17 and identified putative ILC3-myeloid cell interactions, including via lymphotoxin-β-LTBR. Altogether, our data provide important insights into the orchestration and execution of type 17 immunity in bladder defense.